Sounds of Life and Concern: Echoing Through Lively Storytelling in Early Childhood Education - Ibanez, Veronica; Tadokoro, Karen; Li, Shuxiao (Sheena); Sze, Long Hei (Icy) (Journal of Childhood Studies, 2024)
This paper emerges from the journey of a group of early childhood educators seeking to reconnect with land in meaningful and ethical ways. Reorienting from humancentric views, the authors explore “lively storytelling” to bring attention to overlooked stories and create alternative ways of being and thinking. We are called into new relations and ecological entanglements through a sensitive and responsive attunement to the soundscapes of Lynn Creek and Hastings Creek in Vancouver and Bow River in Calgary. Our engagement encompasses a posthumanist framework while weaving interdisciplinary studies in environmental humanities, materiality, and architecture to encourage generative inquiries and dialogue in early childhood classrooms and communities.